Diversity of Collembola in The Benang Kelambu Waterfall Natural Tourism Attraction Area Rinjani Geopark Lombok Island - Siti Raudatul Zuhriah; Mukhlis; Mohammad Liwa Ilhamdi (Jurnal Biologi Tropis, 2023)
Collembola or what is known as springtails are insects that live in the soil, soil surface, leaf litter and litter surfaces. Collembola has an important role in the nutrient cycle, decomposition of organic material and plays a role in soil formation which is important for forest ecosystems. Collembola diversity in the Benang Kelambu Waterfall Natural Tourism Attraction Area, Rinjani Geopark, Lombok Island has never been done. This research aims to determine the diversity and ecological index of Collembola in the Benang Kelambu Waterfall Geopark Rinjani Natural Tourism Attraction Area. The type of research used was Quantitative Descriptive research conducted on 14 July-12 August 2023. Sampling used the Pitfall trap method with two research stations. Samples were taken 4 times over 1 month. The data analysis techniques used include the Sannon-Wienner diversity index (H'), the Evennes evenness index (E) and the Simpson dominance index (Di). The research results obtained 3 sub orders, 7 families, 19 species with 1657 individuals. The results of the analysis show that the Collembola Diversity Index H'=1,89591 is in the medium diversity category, the Evenness Index E=0,6439 is in the medium population evenness category and the Dominance Index Di=0,22118 is in the no dominant species category.